2004
DOI: 10.1242/jcs.01097
|View full text |Cite
|
Sign up to set email alerts
|

Chronic oxidative stress compromises telomere integrity and accelerates the onset of senescence in human endothelial cells

Abstract: Replicative senescence and oxidative stress have been implicated in ageing, endothelial dysfunction and atherosclerosis. Replicative senescence is determined primarily by telomere integrity. In endothelial cells the glutathione redox-cycle plays a predominant role in the detoxification of peroxides. The aim of this study was to elucidate the role of the glutathione-dependent antioxidant system on the replicative capacity and telomere dynamics of cultured endothelial cells. Human umbilical vein endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
278
5
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(311 citation statements)
references
References 55 publications
13
278
5
6
Order By: Relevance
“…The free‐radical theory of aging posits that degenerative senescence is largely the result of the cumulative effect of ROS (Haendeler et al ., 2003; Kurz et al ., 2004), and the present study demonstrates that PPKO induced ROS generation in 30 min (Fig. 3) and that the antioxidants NAC and TEMPO abrogated PPKO‐induced SA‐β‐gal staining in young HDFs (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The free‐radical theory of aging posits that degenerative senescence is largely the result of the cumulative effect of ROS (Haendeler et al ., 2003; Kurz et al ., 2004), and the present study demonstrates that PPKO induced ROS generation in 30 min (Fig. 3) and that the antioxidants NAC and TEMPO abrogated PPKO‐induced SA‐β‐gal staining in young HDFs (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…The involvement of ROS in degenerative senescence has been proposed previously (Beckman & Ames, 1998; Haendeler et al ., 2003; Kurz et al ., 2004). To investigate the molecular mechanism for PPKO‐induced cellular senescence, we examined whether PPKO induces the accumulation of ROS in young HDFs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telomere attrition is accelerated as the cell ages or faces stress. [42][43][44] Indeed, in senescent PAECs, the amount of Rap1 in the cytosol is elevated compared with young PAECs. 37 Thus, it is tempting to speculate that as telomere length is reduced, the ratio between telomere-bound and "free" Rap1 (available for the cytoplasmic activation of the NFkB pathway) is affected.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quantitation by real-time PCR showed that telomerase activity in BMhTERT clones was comparable with a number of tumor cell lines (additional data not shown). One likely explanation for shortening of mean telomere length in BMhTERTs is that oxidative stress overrode the lengthening capacity of telomerase (49). Mounting evidence indicates that the length of a subset of the shortest telomeres, rather than the average length of the telomeres, predicts proliferative arrest (50).…”
Section: Discussionmentioning
confidence: 99%